2018
DOI: 10.1002/ps.4862
|View full text |Cite
|
Sign up to set email alerts
|

Mass trapping designs for organic control of the Japanese beetle, Popillia japonica (Coleoptera: Scarabaeidae)

Abstract: The mass trapping designs captured high numbers of adult P. japonica, while comparatively few adults and little damage to the foliage were recorded on plants. Mass trapping may provide effective alternative management options for P. japonica with less or no insecticides applied to the crop. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…In China, Chen et al () used funnel traps to mass trap Popillia quadriguttata , a closely related species to P. japonica , and obtained a reduction of 93% of adults and 90% of soil larvae. Piñero and Dudenhoeffer () reported that odor‐baited traps with larger beetle‐holding capacity positioned at the perimeter of blueberry and elderberry orchards collected over 10.3 million P. japonica adults in a 3‐year period. Consistently, beetle densities and levels of feeding damage caused to elderberry and particularly to blueberry plants were comparatively low for all the years taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, Chen et al () used funnel traps to mass trap Popillia quadriguttata , a closely related species to P. japonica , and obtained a reduction of 93% of adults and 90% of soil larvae. Piñero and Dudenhoeffer () reported that odor‐baited traps with larger beetle‐holding capacity positioned at the perimeter of blueberry and elderberry orchards collected over 10.3 million P. japonica adults in a 3‐year period. Consistently, beetle densities and levels of feeding damage caused to elderberry and particularly to blueberry plants were comparatively low for all the years taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, once proven with a dedicated experiment that LLINs are effective under field application against P. japonica , the use of lured attract‐and‐kill devices, such as Trinet, would provide useful advantages in the management of beetle outbreaks: avoiding the need of a continuous emptying of traps, the system would be effective throughout the season (only pheromone replacement would be necessary), with a trapping capability that would not be affected by limitations in volume of collecting jars. Furthermore, this approach would avoid the odor of collected decaying dead beetles that may interfere with the pheromone attractiveness and eventually with beetle capture (Alm et al ; Piñero and Dudenhoeffer ). In this regard, a study on the attractiveness of an LLIN lured device is currently in progress to explore the potential knock‐down effect on the local population of the Japanese beetle.…”
Section: Discussionmentioning
confidence: 99%
“…For horticultural pests, mass trapping is another technique that may be more cost-effective for small-scale growers than for those with larger acreages, provided that systems can be developed that capture sufficient numbers of the target pest(s) before they can reproduce or damage the crop [118]. For example, an experimental mass-trapping technique developed for managing Japanese beetle ( Popillia japonica Newman) (Coleoptera: Scarabaeidae) on small-scale fruit farms captured very high numbers of beetles (more than 10 million over three years) and kept crop damage low [119]. In a novel extension of this strategy, the collected beetles were subsequently composted and converted into high-quality soil amendments that could help offset the costs of the traps and lures [120].…”
Section: Opportunities: Factors Favoring Adoption and Development mentioning
confidence: 99%
“…In Missouri, a mass trapping system was developed to control Japanese beetle, Popillia japonica (Coleoptera: Scarabaeidae) in organic systems. This mass trapping system has proven effective when implemented in blueberry and elderberry orchards (Piñero and Dudenhoeffer, 2018). Using this IPM system, by deploying 15 mass trapping devices at each of two farms (<1.4 Ha total area), several hundred kilograms of Japanese beetle carcasses have been collected on a yearly basis (Piñero and Dudenhoeffer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This mass trapping system has proven effective when implemented in blueberry and elderberry orchards (Piñero and Dudenhoeffer, 2018). Using this IPM system, by deploying 15 mass trapping devices at each of two farms (<1.4 Ha total area), several hundred kilograms of Japanese beetle carcasses have been collected on a yearly basis (Piñero and Dudenhoeffer, 2018). Given the high N content of insects, composting Japanese beetle carcasses could represent a positive way of utilizing such large amounts of this biomass generated on-farms.…”
Section: Introductionmentioning
confidence: 99%